2017
DOI: 10.3389/fmicb.2017.02578
|View full text |Cite
|
Sign up to set email alerts
|

Role of the DNA Mismatch Repair Gene MutS4 in Driving the Evolution of Mycobacterium yongonense Type I via Homologous Recombination

Abstract: We recently showed that Mycobacterium yongonense could be divided into two genotypes: Type I, in which the rpoB gene has been transferred from Mycobacterium parascrofulaceum, and Type II, in which the rpoB gene has not been transferred. Comparative genome analysis of three M. yongonense Type I, two M. yongonense Type II and M. parascrofulaceum type strains were performed in this study to gain insight into gene transfer from M. parascrofulaceum into M. yongonense Type I strains. We found two genome regions tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…The pronounced difference in a number of unshared genes among the M. yongonense genomes highlights the possibility of extensive HGT from outside the cell in these genomes. Evidence of HGT among NTM members has been described previously (Kim et al, 2016(Kim et al, , 2017Fedrizzi et al, 2017;Kim et al, 2013b).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…The pronounced difference in a number of unshared genes among the M. yongonense genomes highlights the possibility of extensive HGT from outside the cell in these genomes. Evidence of HGT among NTM members has been described previously (Kim et al, 2016(Kim et al, , 2017Fedrizzi et al, 2017;Kim et al, 2013b).…”
Section: Discussionmentioning
confidence: 71%
“…The substantial difference between the M. yongonense RT 955-2015 rpoB sequence and that of M. parascrofulaceum and M. yongonense 05-1390, while showing high similarity to M. intracellulare and its closely related species (M. chimaera DSM 44623, M. paraintracellulare KCTC 290849), is additional evidence that the RT 955-2015 strain belongs to the Type II genotype group. Kim et al used genome-based phylogenetic analysis to classify M. yongonense species into two distinct genotypes (Type I genotype and Type II genotype) (Kim et al, 2016), and demonstrated that Type I genotype has laterally acquired rpoB from M. parascrofulaceum while Type II genotype possess the M. intracellulare rpoB gene (Kim et al, 2016(Kim et al, , 2017. Kim (Kim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently identified a novel human pathogenic member of the M. avium complex, Mycobacterium yongonense ( 32 ). By conducting a genome analysis of M. yongonense DSM 45126 T ( 33 37 ), we also introduced a novel Mycobacterium–Escherichia coli shuttle vector system using the mycobacterial replicon of pMyong2, which is a linear plasmid within its genome that can lead to increased heterologous gene expression in recombinant M. smegmatis (rSmeg) and rBCG compared to that using the conventional pAL5000 vector system which was originated from M. fortuitum ( 38 , 39 ). Furthermore, we showed that rSmeg expressing HIV-1 p24 Gag using a pMyong2 vector system led to the enhanced immune responses against HIV-1 p24 Gag in mice, compared to rSmeg in the pAL5000 vector system or using an integrative plasmid, pMV306 system, suggesting the feasibility of the pMyong2 vector system in rSmeg vaccine application ( 40 ).…”
Section: Introductionmentioning
confidence: 99%